DORNASE ALPHA: THREE CLINICAL EFFECTS - O.I. Simonova (Педиатрическая фармакология, 2008)
Chronic diseases of lungs are characterized by the presence of mucostasis which is the reason for often aggravations of bron chopulmonary process and favors progression of the disease. The article convincingly shows the necessity of inclusion mucolytic therapy in baseline therapy in the treatment of such diseases. Detailed information is given about the ferment medication dornase alpha, its not very well known but very important non mucolitic properties, such as anti inflammatory and antibacterial. The author provides recommendations on its correct use, because performance of the rules may determine the efficiency of therapy.Key words: mucoviscidosis, chronic bron chopulmonary diseases, mucostasis, treatment, dornase alpha, children.